Medical Ethics : A Very Short Introduction - Hope, Tony (Oxford Oxford University Press, 2004)
In this Very Short Introduction, Tony Hope deals with a range of thorny moral questions, some of which are age-old, like euthanasia and the morality of killing, and others of which have arisen with recent advances in medical technology." "Tony Hope also explores political questions, discussing how health-care resources can be fairly allocated, and addressing controversial problems such as: Should treatment for mental illness be imposed on patients without their consent? Should post-menopausal women have access to assisted reproduction technologies? And who should have the right to access information from genetic testing?
Include Illustrations, Index, Notes and References.
A Very Short Introduction.
Keywords: Medical ethics